BENTUK DAN MAKNA RAGAM HIAS PADA TIANG INTERIOR RUANG NDALEM ROEMAHKOE HERITAGE HOTEL LAWEYAN SOLO - Henny Tri Hastuti Hasana; Dea Syahnas Paradita; Dina Kristiana Seftianingsih; Muhammad Dian Rifai (Akademi Seni dan Desain Indonesia Surakarta, 2024)
The form and meaning of decorative variations in space-forming and space-filling elements are one way to shape the interior character of a space and is one way to find out the style used in an interior space. The use of decoration often adapts to economic capabilities and social position in society. Decoration is something designed to add beauty to a building. One way is to implement these decorations on the interior elements of a building. The results of this research aim to find out what forms of decoration are used, as well as the meaning they contain. Qualitative research with a form and meaning study approach, the study approach was carried out on the decoration on the interior pillars of the ndalem room of the Roemahkoe Heritage Hotel Laweyan Solo. This research uses a qualitative descriptive method with a form and meaning approach as a basis for analysis. The decorative form of the lung lungan is very clearly visible on the pillars in the interior of the ndalem room of the Roemahkoe Heritage Hotel, which has the meaning of the dignified behavior of Javanese society in their daily lives. The comparative method is also used to compare with other similar objects. Data collection techniques using; literature study, observation and interviews, using interpretive analysis Key words : Decorative styles_Interior_Roemahkoe Heritage_ Laweyan Solo